A Case of Myocardial Rupture on the Background of Coronary Artery Thrombosis - Hirachan, N; Maharjan, M (Journal of Gandaki Medical College-Nepal, 2018)
Myocardial infarction infrequently complicates with the rupture of myocardial free wall in 6.2% of cases. It represents the second cause of death after cardiogenic shock, and accounts for as much as 15% of in-hospital mortality. The authors here report a case of an 80 year old male with the cause of death as myocardial rupture on the background of coronary artery thrombosis. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 68-70